Leadership Traits and Villages' Involvement in Community Development Projects in Dangkor District, Cambodia - Norith, Ma (1997)
This study was to examine the results of agency-motivated projects, particularly in terms of the role of village leaders and how leadership traits related to the involvement of the villages. The agency in question was Redd Barna, a voluntary organisation, which extended financial and expert assistance. The study focused at three major projects viz., rice, water, and cow projects. Specific objectives of the study were to examine the leadership qualities and the level of involvement of the villages in community development projects. Further, the study examined the relationship of the leadership traits (qualities and demographic characteristics) and the involvement level of the villages, as perceived by the leaders themselves. The sample of the study was 27 village headmen or chairmen of Village Development Committees (VDCs). Structured questionnaires formed the main instrument for data collection supported by informal interviews, personal observations and secondary sources. The overall profile of leaders could be summed up as democratically oriented with moderate to high leadership behaviour characteristics and high leadership situation characteristics. The majority of the leaders fell into the group with a high level of overall leadership qualities, while the rest belonged to the moderate level of overall leadership qualities. On the whole the level of involvement of the villages. in the three selected projects was moderate. Among the non-focused projects, the latrine project presented specific implication worth noting. There was a high degree of willingness and involvement in construction, but the project failed because the people abandoned the latrines. This implies the need to educate the people and affect attitudinal changes. Leadership qualities had some bearing on the leaders' own assessment of their own villages' involvement in projects. Generally they indicated that the involvement level was low and moderate in the various stages of the projects. However, the democratic leaders, and those with high leadership situation were more favourable in their assessment of their villages' level of involvement.The leaders with high overall leadership qualities perceived the villages' involvement level to be mainly moderate, indicating that leaders who themselves were categorically of high leadership quality did not necessarily place their villages at the top level in terms of involvement. This in turn seemed to suggest that generally, very good leaders tend to expect a higher standard of performance in their villages. Most of them thought their villages as only moderately involved. From the findings of the study, it was concluded that the Redd Barna projects had attained a measurable success while the village leaders had proved to possess the potentials to facilitate the programme of development of the villages with their overall favourable leadership traits. To enhance the success of the projects, a number of recommendations were presented: (i) The decision on what projects are to be implemented in any village should be made on the basis of a comprehensive study on many aspects including people's needs, environmental suitability and organisational capability. (ii) To ensure the successful involvement of the people in the projects, there is a need to accelerate the existing non-formal education programme, particularly in the form of continuous extension work. (iii) A co-ordinating committee should be formed in each district to bring together government agency officials, the Redd Barna personnels and the village leaders. This committee should serve as a linkage between the people and the project sponsors.